English Language Teaching in Indonesia: Monolingual and Multilingual Practices - Naufal Fachrur Rozi (k@ta: A Biannual Publication on the Study of Languange and Literature, 2023)
21st century urges one’s ability to tacitly navigate the increasingly complex linguistic spaces of this modern world and it results in super diverse society (Gallagher, 2020). Kachru’s (1986, as cited in Wardhaugh & Fuller, 2015) arrives with the conceptual framework named world of Englishes. It becomes such pivotal consideration to drive today’s language ideology, including Indonesian. This literature review then aims at unveiling Indonesian EFL teachers’ views about monolingual and multilingual practices by capitalizing English language teaching classroom as the context. Data were derived from relevant research reports that meet the criteria. Criteria comes in threefold. They were conducted in any range of time, were obtained from catch-all indexing, and were done in Indonesian setting. The findings come in agreement that both monolingualism and multilingualism yielded two camps: justifying it and rejecting it in Indonesian EFL context. Implication is then needed to further validate it in accordance with empirical research’s result.